The public life of privacy in nineteenth-century American literature - Margolis, Stacey, 1966- (New Americanists., 2005)
Challenges the familiar way of reading a major strain of 19th century American literature. Rather than seeing this strain as preoccupied with a subject's inner mental life, it shows that subjects can only be understood, and understand themselves, through.